Pengaruh Etos Kerja dan Disiplin Kerja terhadap Kinerja Pegawai pada Dinas Penanggulangan Kebakaran dan Peyelamatan Provinsi DKI Jakarta - Budianto, Eko; Kristanto, Rudi (Reformasi Administrasi, 2023)
This study aims to analyze the influence of work ethic and work discipline on employee performance at the Fire Fighting and Rescue Department of DKI Jakarta Province. The research employs a survey method with quantitative analysis. The objective is to determine the extent of the impact of work ethic and work discipline, both partially and collectively, on employee performance.Using SPSS version 22 for data analysis, the results indicate that: (1) Partially, the t-test reveals that work ethic has a positive and significant effect on employee performance, as the t-count exceeds the t-table value. (2) Similarly, work discipline also shows a positive and significant influence on employee performance, with the t-count higher than the t-table. (3) Simultaneously, the F-test demonstrates that work ethic and work discipline together have a positive and significant impact on employee performance, as the F-count is greater than the F-table.These findings suggest that improving work ethic and work discipline can enhance employee performance in the organization.